Probiotics in endodontics as a biotherapeutic alternative: review of the literature - Quintero-Rojas , Jormany (2025)
Probiotic therapy in endodontics emerges as a promising biotherapeutic strategy to modulate the microbiota of the root canal system, prevent microbial recolonization, and promote pulp-periapical health. Probiotics, defined as live microorganisms that confer health benefits to the host, have demonstrated antimicrobial and immunomodulatory effects, in addition to competing for nutrients and adhesion sites against endodontic pathogens such as Enterococcus faecalis and Candida albicans. The reviewed evidence includes in vitro, in vivo, and clinical studies, highlighting the ability of strains such as Lacticaseibacillus rhamnosus, Limosilactobacillus reuteri, Lactiplantibacillus plantarum, Lacticaseibacillus casei, and Bifidobacterium species to inhibit pathogens in both planktonic and biofilm phases, with efficacy comparable to traditional irrigants and intracanal medication but with lower cytotoxicity. Additionally, bacterial metabolites have been observed to enhance the action of conventional antimicrobials or act independently. However, variability in efficacy among strains, delivery vehicles, and experimental conditions underscores the need to standardize protocols and validate their application in clinical contexts. This review concludes that probiotics and their metabolites represent a biosafe and sustainable alternative, with the potential to complement or partially replace antimicrobial agents in endodontic practice.